Base Excision Repair in the Immune System: Small DNA Lesions With Big Consequences - Stratigopoulou, Maria; van Dam, Tijmen P.; Guikema, Jeroen E. J. (Frontiers in Immunology, 2020)
The integrity of the genome is under constant threat of environmental and endogenous agents that cause DNA damage. Endogenous damage is particularly pervasive, occurring at an estimated rate of 10,000–30,000 per cell/per day, and mostly involves chemical DNA base lesions caused by oxidation, depurination, alkylation, and deamination. The base excision repair (BER) pathway is primary responsible for removing and repairing these small base lesions that would otherwise lead to mutations or DNA breaks during replication. Next to preventing DNA mutations and damage, the BER pathway is also involved in mutagenic processes in B cells during immunoglobulin (Ig) class switch recombination (CSR) and somatic hypermutation (SHM), which are instigated by uracil (U) lesions derived from activation-induced cytidine deaminase (AID) activity. BER is required for the processing of AID-induced lesions into DNA double strand breaks (DSB) that are required for CSR, and is of pivotal importance for determining the mutagenic outcome of uracil lesions during SHM. Although uracils are generally efficiently repaired by error-free BER, this process is surprisingly error-prone at the Ig loci in proliferating B cells. Breakdown of this high-fidelity process outside of the Ig loci has been linked to mutations observed in B-cell tumors and DNA breaks and chromosomal translocations in activated B cells. Next to its role in preventing cancer, BER has also been implicated in immune tolerance. Several defects in BER components have been associated with autoimmune diseases, and animal models have shown that BER defects can cause autoimmunity in a B-cell intrinsic and extrinsic fashion. In this review we discuss the contribution of BER to genomic integrity in the context of immune receptor diversification, cancer and autoimmune diseases.